Pengaruh Psikoedukasi terhadap Pengetahuan dan Tingkat Kecemasan Pasien dengan hipertensi - Omi Haryati; Nurdiana Nurdiana (Poltekkes Kemenkes Jakarta III, 2018)
Psychoeducation is the provision of information about managing disease and the psychological aspects of patients. Psychoeducation teaches someone about a problem so they can reduce the stress associated with the problem. Relaxation can reduce muscle tension, saturation and anxiety so as to prevent the increase in pain stimuli and can help hypertensive patients to reduce anxiety and strengthen individual coping. This study aims to determine the effect of psychoeducation on the knowledge and anxiety level of patients with hypertension. The study design was a quasi-experimental pre-post test with control group psychoeducation intervention with a sample of 80 people. The results were significant differences in the knowledge of patients before and after the intervention group (p value knowledge = 0.013), whereas in the control group there was no difference (p value = 0.770). The conclusion is obtained that psychoeducation can improve the knowledge of patients with hypertension, so that it is expected to be one form of intervention that can be applied to the community in the Cipayung District area.